The Effect of Service Quality toward Customer Satisfaction of Go-Jek Online Transportation: A Case Study of Students at Syiah Kuala University, Indonesia. (March 2020) - Amiruddin,; Nazaruddin,; Jamil, T.M.; Andika, Yessi Hajri
Abstract: This study aimed to determine the service quality and customer satisfaction of GO-JEK online transportation. This research used quantitative descriptive methods. After doing the literature and field reviews, the data in this study collected through questionnaires totaling 86 respondents. The sampling technique in this study used the incidental sampling technique. Data analysis techniques used were simple linear regression, correlation coefficient, determination, t-test to test and prove the research hypothesis. Based on the results of data analysis, the results of the study showed correlation 0.634, which means the strong correlation between variables of service quality with customer satisfaction variables. The coefficient of determination showed the effect of service quality on customer satisfaction of 0.796 or 79.6%. Furthermore, the t-test at the 5% significance level of the hypothesis was accepted, evidenced by the probability value. The conclusion from this study is that there is an influence between service quality and customer satisfaction. If the service quality provided is good, it will create customer satisfaction.